2008
DOI: 10.1177/0193945907311324
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Coping of Midlife Women in Divorce Transition

Abstract: This article describes stress and coping by decider status. Participants were 154 women aged 34 to 54 years who were recently divorced from their first marriage and were married 3 years prior to divorce. Participants self-selected into decider statuses as initiators, noninitiators, or mutual deciders. Noninitiators indicated not knowing the divorce experience was going to occur, not having enough time to get ready for it, saw it as something someone else did, and perceived it as a threat. Initiators and mutual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Variation in partner availability may also help explain why remarriage tends to occur more quickly for initiating than noninitiating partners in divorce (Sweeney, 2002), as evidence suggests that the existence of large pools of possible new marriage partners may factor into a decision to divorce (South & Lloyd, 1995). Initiators may also be further along in the postdivorce adjustment process and thus better prepared to reconnect (e.g., Sakraida, 2008; Vaughan, 1986), although these two groups tend to experience similar levels of depressive symptoms after a marriage ends (Sweeney & Horwitz, 2001). Regardless of the mechanisms at work, these studies point to potential sources of selectivity in the preexisting characteristics of individuals who remarry or repartner.…”
Section: The Demography Of Remarriagementioning
confidence: 99%
“…Variation in partner availability may also help explain why remarriage tends to occur more quickly for initiating than noninitiating partners in divorce (Sweeney, 2002), as evidence suggests that the existence of large pools of possible new marriage partners may factor into a decision to divorce (South & Lloyd, 1995). Initiators may also be further along in the postdivorce adjustment process and thus better prepared to reconnect (e.g., Sakraida, 2008; Vaughan, 1986), although these two groups tend to experience similar levels of depressive symptoms after a marriage ends (Sweeney & Horwitz, 2001). Regardless of the mechanisms at work, these studies point to potential sources of selectivity in the preexisting characteristics of individuals who remarry or repartner.…”
Section: The Demography Of Remarriagementioning
confidence: 99%
“…Although research that has examined the period of adaptation to life following divorce (Chiriboga, 1982;Davis & Aron, 1988;Deckert & Langelier, 1978;Uhlenberg, Cooney, & Boyd, 1990;Weingarten, 1989) as well as the impact of late-life divorce on children (Greenwood, 2012;Pett, Lang, & Gander, 1992;White, 1990) and women (Cain, 1988;McDaniel & Coleman, 2003;Sakraida, 2008;Thomas & Ryan, 2008;Uhlenberg et al, 1990), less research has focused on an in-depth understanding of how people going through divorce in late life experience and retrospectively view the divorce process. Qualitative studies in this area also typically focus on the experiences of women (McDaniel & Coleman, 2003;Rokach et al, 2004;Thomas & Ryan, 2008) and rarely give voice to the experiences of men.…”
Section: Reasons For Divorce In Mid-to Later Lifementioning
confidence: 99%
“…In addition, our results showed that women suffer more from divorce than men. Thus, clinical treatments should be provided to women to be able to cope with divorce transition (Sakraida, 2008).…”
Section: Discussionmentioning
confidence: 99%